2022
DOI: 10.1007/s10072-022-06050-7
|View full text |Cite
|
Sign up to set email alerts
|

Striatal dopamine transporter imaging in Parkinson’s disease drug-naïve patients: focus on sexual dysfunction

Abstract: Introduction Dopamine is involved in sexual behavior, but dopaminergic imaging studies establishing the relationship between nigrostriatal dopaminergic degeneration and sexual dysfunction (SD) in Parkinson’s disease (PD) are lacking. Methods We retrospectively analyzed clinical and 123I-FP-CIT SPECT data of 43 drug-naïve PD patients. Based on the sexual function domain of the Non-Motor Symptoms Scale (NMSS), we identified 23 patients with sexual concerns (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 45 publications
2
6
0
Order By: Relevance
“…Previous studies reported that striatum SBR was associated with autonomic dysfunction in PD patients, 1821 which was consistent with our findings observed in current study. We revealed FC between left M1 and bilateral middle cingulate gyri mediated the effects of striatal dopamine depletion on autonomic dysfunction, suggesting impaired left M1 subnetwork also contributed to autonomic dysfunction in PD patients.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Previous studies reported that striatum SBR was associated with autonomic dysfunction in PD patients, 1821 which was consistent with our findings observed in current study. We revealed FC between left M1 and bilateral middle cingulate gyri mediated the effects of striatal dopamine depletion on autonomic dysfunction, suggesting impaired left M1 subnetwork also contributed to autonomic dysfunction in PD patients.…”
Section: Discussionsupporting
confidence: 94%
“…7072 In this study, striatum SBR was negatively associated with SCOPA-AUT scores, which was consistent with previous studies showing autonomic dysfunction in PD was associated with striatal dopamine depletion. 1821 Cognitive impairment was also one of the most common non-motor features of PD patients 73 and associated with disease progression and outcome. 7375 Cognitive impairment could occur at the early stage and even prodromal phase of PD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drosophila has been widely used as a model animal to study NDDs like PD as they share the same types of neurotransmitter systems like gamma-aminobutyric acid (GABA), glutamate, DA, serotonin, and acetylcholine, and can perform complex behaviors viz., sexual display, social behavior, and learning ( Botella et al, 2009 ). SD in PD seemed to be multifactorial with no single cause identified ( Brown et al, 1990 ) but the involvement of DA remains one of the most important factors ( Heaton, 2000 ; Contaldi et al, 2022 ). However, very little is known about the SD mechanisms involved in sporadic PD.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that DA in the hypothalamus plays a role in regulating sexual behaviors, however, the detailed mechanism of SD in PD is not known ( Sakakibara et al, 2011 ). A study reported the relationship between the severity of SD and specific patterns of nigrostriatal dopaminergic (DAergic) denervation (especially involving both putamina) in newly diagnosed drug-naïve PD patients ( Contaldi et al, 2022 ). The understanding of the function and regulation of the behavioral circuits involved in mating will have potential implications for the medical treatment of SD in humans ( Emmons and Lipton, 2003 ).…”
Section: Introductionmentioning
confidence: 99%